Analysis of Management Strategies for Village-Owned Enterprises (BUMDes) in Rumah Tiga Village, Teluk Ambon District - Swarty, Robert Sebastianus; Siwalette, Jetter D.; Lawalata, Marfin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the management strategies of Village-Owned Enterprises (BUMDes) in Negeri Rumah Tiga, Teluk Ambon District. The sampling method used was purposive sampling, with informants consisting of three individuals directly involved in the management of BUMDes Tuniwaya: the Director, the Secretary, and the Supervisor of BUMDes. Data collection was conducted through observation, Focus Group Discussions (FGD), and documentation. Data analysis was performed descriptively using qualitative methods with SWOT, IFAS, and EFAS analysis tools. The results indicate that BUMDes Tuniwaya has strong potential for development due to solid legal support and active backing from the village government. Effective management, reflected in the responsible leadership of the director, is a significant asset. However, BUMDes also faces significant challenges, including limited capital, human resources, physical infrastructure, and inadequate promotional media. Internal factor analysis shows a score of 2.90, indicating the need to address weaknesses to improve performance. An EFAS score of 3.80 suggests good opportunities to leverage cooperation with BULOG and marketing through social media. To achieve its maximum potential, BUMDes needs to focus on resource development and increasing community awareness of its benefits